2003
DOI: 10.1007/s00122-003-1445-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait locus analysis of fungal disease resistance factors on a molecular map of grapevine

Abstract: A full-sibling F1 population comprising 153 individuals from the cross of 'Regent' x 'Lemberger' was employed to construct a genetic map based on 429 molecular markers. The newly-bred red grapevine variety 'Regent' has multiple field-resistance to fungal diseases inherited as polygenic traits, while 'Lemberger' is a traditional fungus-susceptible cultivar. The progeny segregate quantitatively for resistances to Plasmopara viticola and Uncinula necator, fungal pathogens that threaten viticulture in temperate ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
190
2
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(203 citation statements)
references
References 42 publications
7
190
2
4
Order By: Relevance
“…Rpv1/Run1 alleles were introduced in V. vinifera by backcrossing (Pauquet et al 2001). The locus Rpv3 was identified on chromosome 18 in the grape variety 'Regent' (Fischer et al 2004) and conferred significant resistance to downy mildew on both leaves and berries in all evaluated years ). In grapevine, this Rpv3 locus was responsible for causing the hypersensitive response (HR) at infection sites within two days after the inoculation (dpi) (Bellin et al 2009, Casagrande et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Rpv1/Run1 alleles were introduced in V. vinifera by backcrossing (Pauquet et al 2001). The locus Rpv3 was identified on chromosome 18 in the grape variety 'Regent' (Fischer et al 2004) and conferred significant resistance to downy mildew on both leaves and berries in all evaluated years ). In grapevine, this Rpv3 locus was responsible for causing the hypersensitive response (HR) at infection sites within two days after the inoculation (dpi) (Bellin et al 2009, Casagrande et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…To date more than thirteen P. viticola major and minor resistance loci have been identified and mapped to chromosomes 4, 5, 7, 8, 9, 12, 14, 17 and 18 (Merdinoglu et al 2003;Fischer et al 2004;Welter et al 2007;Bellin et al 2009;Marguerit et al 2009;Zyprian et al 2009;Moreira et al 2011;Schwander et al 2012). Many of these loci were originally reported without specific gene names some of which were later assigned names in the catalogue of mapped resistance loci (http://www.vivc.de), leaving a few reported loci unnamed.…”
Section: Introductionmentioning
confidence: 99%
“…This region was also identified in an S1 population of M. rotundifolia 'Regale' (Blanc et al 2012). A cross between the resistant 'Regent' and susceptible 'Lemberger' yielded a resistance locus in the same region as Rpv2 (Fischer et al 2004;Welter et al 2007), but since 'Regent' does not have any M. rotundifolia ancestors (Eibach and Töpfer 2003) this locus is assumed to be different from Rpv2 and has therefore been designated Rpv3. Zyprian et al (2009) reported a major resistance locus on chromosome 18 of 'Villard Blanc', which was also detected in a Villard Blanc-derivative, 'Gf.Ga-52-42' (Schwander et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence a specific task is to create an offspring of Grüner Veltliner that combines the estimated wine profile with some resistance genes derived from other Vitis species [5]. Seyval blanc, Villard blanc, or in our case, Malverina could function as resistance donors and they were applied as crossing partners [6]. These donor vines show satisfying stability in the field but still lack adequate wine quality.…”
Section: Introductionmentioning
confidence: 99%